Subnational identities in the context of the changing internalgeopolitics. The case of post-revolutionary Ukraine - Mihaylov Valentin; Sala Stanisław (Bulletin of Geography. Socio-Economic Series, 2018)
The main changes in the development of identity of Ukrainians after the Euromaidan revolution and their influence on internal geopolitics of the state are presented in the paper. The authors have made a critical overview of the key psychological and symbolic domains of Galician and Little-Russian identity, drawing attention on their changes in the context of the current geopolitical conflict which led to the loss of territory in 2014. Throughout all the 20th century and nowadays, these identities form the political and cultural landscape of Ukraine and generate a number of social divisions. Apart from those identity issues and their preconditions, the obstacles for the realisation of the policy of Ukrainian nation-building are also discussed. The authors conclude that there is a tendency to strengthen the role of the Ukrainian language and break the ties with Russia in a radical way as well as expansion of the pro-Western attitudes and expectations. In terms of mentality and civilizational values, the widening gap between millions of Russians and Russian-speaking Ukrainians from the East and the population of the central and western regions of Ukraine is also pointed out.